Evolution of the Food Web in Bandon Bay, the Gulf of Thailand: Ten Years of the Blue Swimming Crab Stocking Programme - Amonsak Sawusdee,; Sontaya Koolkalya,; Thanitha Thapanand,; Tuantong Jutagate, (Tropical Life Sciences Research, 2023)
The ecosystem of Bandon Bay, in the Gulf of Thailand (GoT), has been impacted since 2007 by the continued stocking of larval blue swimming crab Portunus pelagicus, also called a crab bank. In this study, the food web in the Bay was modelled using Ecopath software to compare the trophic status, interaction and energy flow among the components in the system in 2007 and 2016 (i.e., before and 10 years after the crab bank intervention). The models were based on data collected from trawling. Twenty fish and shellfish components were used in the 2007 model, while 22 were used in the 2016 model. A significant increase in biomass was found in blue swimming crab, but biomass declined for other demersal fishes, cephalopods, and Penaeid shrimps. The production/biomass ratios of most components were higher in 2016 but the consumption/biomass ratios were relatively unchanged. The ecotrophic efficiency indicated that shellfishes were more exploited than fishes. Changes in most of the ecological indices revealed higher maturity and stability after 10 years of crab bank operation. The mixed trophic impact indicated bottom-up regulation, and that the increase of blue swimming crab negatively impacted only Mantis shrimp. Overall, the results indicate positive impacts of the crab bank intervention.